(untitled) (Nonlinear Studies, 2022)
This paper intends to propose a general approach established to control the states of some classes of fractional-order discrete neural networks. For this reason, a novel influential result is set up and theoretically derived in light of the Lyapunov direct method in order to assure the accomplishment of the desired stabilization for those classes under consideration. The influence of such stabilization approach is validated through some performed numerical simulations.